IMPLEMENTASI E-ARSIP PADA KANWIL KEMENTERIAN AGAMA PROVINSI BENGKULU - Bendriyanti, Rita Prima; Zulita, Leni Natalia (UNIVED Press, 2012)
Making E - Records Implementation at the Regional Office of the Ministry of Religion is strived for perfection in the administration of archives that has not be integrated , systemic , and often comprehensive document management - document remains piecemeal by sections - sections , recording archives - still manually archive all of which are not apart from the common understanding and interpretation of the records are still limited and narrow by various groups , including among state officials to make the job was not effective and efficient when faced with the need for quick information . Data collection method used is through observation and literature and the latter is making software through a structured analysis and design .Based on a review of theory, analysis, and implementation is done on the conclusion that the Archives has the functionality and usefulness in supporting the activities of the state and the implementation function adininistrasi - management functions , in addition to the information in the records should be maintained in a system called records management ( e - Archive ) which is the management of the entire data file , so that later in the process of data retrieval and archival information becomes easier , quite accurate and quite valid , and can assist the organizers in accordance with archival principles , kaedah and archival standards .Keywords : E - Archive , Implementation